PENGUKURAN TINGGI, DIAMETER DAN VOLUME TANAMAN JATI (Tectona grandis Linn f. ) UMUR 7 TAHUN DI AREAL PT. UNITED TRACTORS, Tbk KELURAHAN LOA BAKUNG KECAMATAN SUNGAI KUNJANG KOTA SAMARINDA - Jufrianto; Agustina Murniyati (Politeknik Pertanian Negeri Samarinda, 2017)
The purpose of this study was to determine the average height, diameter and average volume of teak trees (Tectona grandis Linn f.) Planted in 2010 at PT. United Tractors, Tbk Kelurahan. Loa Bakung District. Kukung River in Samarinda City. The results of this study are expected to be taken into consideration for the development of teak plants (Tectona grandis Lnn.f.), Especially in East Kalimantan. The measurement results of teak plants (Tectona grandis Linn.f) aged 7 years were 200 trees with a spacing of 2 m x 2 m with an area of ​​800 m2 in the area of ​​PT. United Tractors Tbk, obtained data on average height of 11.381 m, with a minimum height of 4.37 m, a maximum height of 18.35 m, a standard deviation of 2.97 m and a coefficient of variation of 26.12%. The average diameter is 11.299 cm, the minimum diameter is 2.81 cm, the maximum diameter is 19.33 cm, the standard deviation is 3.31 cm, and the coefficient of variation is 29.37%, the average volume data is 0.095 m3, the minimum volume is 0.002 m3 , the maximum volume is 0.264 m3, the standard deviation is 0.0958 m3, and the coefficient of variation is 62.02%.